1997
DOI: 10.1038/sj.hdy.6881710
|View full text |Cite
|
Sign up to set email alerts
|

Novosibirsk revisited 24 years on: chromosome polymorphism in the Novosibirsk population of the common shrew Sorex araneus L.

Abstract: A Robertsonian fusion polymorphism in the common shrew (Sorex araneus L.), first described in Academgorodok near Novosibirsk (western Siberia) in 1970-72, was re-examined in . The polymorphism in the 1970s involved chromosome arm combinations go, ji, mp and qr, i.e. each of these combinations was present in both a metacentric and a twin-acrocentric state in the population at that time. The twin-acrocentric morph for go occurred at low frequency in 1970-72 and was not observed in 1994-95. The polymorphism for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Shrews were trapped over 1998–2006 by home‐made live‐traps (Shchipanov, 1986) and pitfalls. Chromosomal data from previous studies of the Novosibirsk and Tomsk races (Kral & Radjabli, 1974; Polyakov et al. , 1996, 1997, 2003) were also used in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Shrews were trapped over 1998–2006 by home‐made live‐traps (Shchipanov, 1986) and pitfalls. Chromosomal data from previous studies of the Novosibirsk and Tomsk races (Kral & Radjabli, 1974; Polyakov et al. , 1996, 1997, 2003) were also used in the analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Some rare diachronic studies have shown that some karyotypic variations may remain stable (in both frequency and type of mutation) at least within the period of the short‐term surveys conducted (e.g. at least 20 generations in Holochilus braziliensis : Nachman & Myers, ; 24 years, corresponding to >24 generations, in Sorex araneus : Polyakov et al ., ). However, when one is interested in longer periods, data are surprisingly few.…”
Section: The Persistence Of Chromosomal Polymorphisms In Mammalsmentioning
confidence: 97%
“…With few exceptions, all the temporal analyses concentrate on the morphological characters of the hybridizing taxa, owing to the scarcity of genetic data in the literature. In fact, only taxa with a long history of genetic studies can be used ( Polyakov et al ., 1997 ). One of these is the house mouse Mus musculus domesticus , which has been the subject of cytogenetic studies since the 1960s ( Gropp et al ., 1969 ; Capanna et al ., 1976 ); its high chromosomal variability leads to a large number of chromosomal races with a diploid number ranging from 2 n = 40, all telocentric chromosomes, to 2 n = 22 with nine Robertsonian (Rb) fusions.…”
Section: Introductionmentioning
confidence: 99%